Analysis of Tec Variations over Nepal Obtained from GPS Data on Geo-Magnetically Quiet and Disturbed Days of the Year 2015 (Journal of Nepal Physical Society, 2021)
Dual frequency Global Positioning System (GPS) receiver in two nearby stations i.e. BESI (28.228 °N, 84.739 °E) and GHER (28.375 °N, 84.739 °E) located at almost same latitude and longitude are used to measure ionospheric total electron content (TEC) for the year 2015. Since Year of 2014- 2016 have been known as most active years in terms of geomagnetic events, the year 2015 shows some abnormal results. Diurnal, monthly and seasonal variations of GPS TEC have been studied. The difference in the value of TEC is observed between quiet and disturbed days. Moreover, the correlation between GPS-data of each month with solar activities parameters such as Kp index, disturbance storm time (Dst) index, and Solar Flux index (F10.7 cm) have been studied, separately for quiet and disturbed days for each station. In case of diurnal variation, mean TEC varies from 0100 UT (LT= UT+5:45) to maximum from 0900 UT to 1100UT. The value of TEC is observed higher on quiet days than disturbed days. For seasonal variation, local seasons i.e. autumn, Spring, Summer and Winter is taken and, the value of TEC is found to be higher in Spring (March, April and May) in both stations in quiet and disturbed days. The difference in value of quiet and disturbed days of GPS-TEC explained the geomagnetic phenomena difference in these days in ionosphere. This study can be useful to calculate the water vapor concentration in the atmosphere which is useful for weather prediction and meteorological department.